An exploratory study of CEO practices in an emerging economy - Johnson, Omobola (Cranfield University, 2013)
This study of CEOs in Nigeria sought to discover the practices that CEOs engaged in as relevant and effective in an emerging economy. Twenty eight CEOs of national and expatriate extraction running national and multi-national companies were interviewed to understand their experiences of the contextual influences of an emerging economy and how this impacted what they did, ie. their practices. In support of contingency theories that seek to explain how effective leadership is the result of appropriateness of fit between particular behaviours and particular situations , CEO practices in an emerging economy were found to be attributable to the macro influences of an emerging economy, discovered in the Nigerian environment to include: - undue government influence, unwholesome competitor practices, short supply of skills and talent, inadequate social and physical infrastructure, a large untapped market and poor government capacity to implement policies and laws. The inclusion of previously unresearched but potentially relevant meso and micro influences of company type and CEO nationality status led to the discovery of additional CEO practices that were perceived to be relevant in an emerging economy context and the attribution of differences in CEO practices to the individual or combined influence of these contexts. A conceptual model derived from the findings of this study provided a new understanding of the relationship between the macro influences of an emerging economy, the meso influence of company type and the micro influence of CEO nationality status on CEO practices and the intended outcomes of those practices. Practical knowledge about the development of business leaders in an emerging economy has been extended as a result of deeper insights into the contextually influenced and relevant CEO practices in an emerging economy.
Keywords: CEOs; business leaders; CEO practices; emerging economy; contextual influences; Nigeria